REVIEWING THE CONSTITUTIONAL RIGHTS ON DEMOCRATIC ELECTION PRACTICES IN INDONESIA AND THE PHILIPPINES - Dachi, Janvencius Valerius Nifowa'azaro; Shahrullah, Rina Shahriyani; Syarief, Elza (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
One form of democracy's embodiment is through general elections. The Philippines and Indonesia are two countries in the Southeast Asian region that are currently still developing their democratic practices through general elections. This study aims to compare how the general elections have been enforced in the two countries to obtain input on the implementation of democracy in Indonesia. The normative legal research design was used in this study, and data collection was carried out through a literature study. The functional comparative approach compares the implementation of general elections in the two countries. The data collected by literature searches were analyzed using a qualitative juridical analysis method. The analysis shows that although the two countries have declared themselves democracies and the general election is the form of their implementation in the constitution, general elections have been used to perpetuate power in both countries. The two countries have differences in implementing general elections due to historical differences and national problems. The most distinguishing matter that can be learned is how the Philippines implemented the general election through the existence of a plebiscite that makes the people more involved in the state process. In addition, information technology in the Philippines' general election has also made the process of conducting the general elections effective and efficient. This study is still limited to analyzing general elections at the national level, especially the presidential and vice-presidential elections. Further research on the general elections of legislature members and regional heads can add to our understanding of the comparative implementation of the two countries.